DOSA ASAL DALAM TRADISI KRISTEN DAN RELEVANSINYA TERHADAP SAKRAMEN BAPTISAN: TINJAUAN DOGMATIS TERHADAP BAPTISAN DARURAT DALAM GEREJA HKBP - Siallagan, Harimerwaty; Marpaung, Frans Soma; Harianja, Mikael; Hasibuan, Ricky Pramono (UPPM Sekolah Tinggi Teologi Tabgha Batam, 2024)
This writing attempts to explore the concept of original sin in Christian theology, which believes that every human inherits a spiritual flaw from the fall of Adam and Eve. The research highlights its impact on the relationship between humans and God, emphasizing the need for salvation through Jesus Christ as the Savior. The main focus is on the sacrament of baptism as a means of forgiveness of sins and spiritual restoration through a new birth in the Christian faith. Through theological analysis, this article discusses the role of emergency baptism, especially in restoring the relationship between humans and God. The author employs a qualitative approach to delve into the concept of original sin and its connection to Baptism. Based on the research findings, salvation through baptism is seen as liberation from original sin and an experience of a new birth. Therefore, emergency baptism in the HKBP church is deemed highly necessary.